Working at doing good: worker identity in career volunteers - Carnes, Rebekah (Kansas State University, 2013)
In the current climate of proliferating nonprofit organizations and demanding social service needs, volunteers play a crucial role. This study looks at career volunteers, who, unlike other types of volunteers, identify with their work as if it were a paying occupation. It examines personal narratives and experiences through interviews in two Kansas communities and in-depth participant observation in one Kansas homeless shelter to find unique identity formation in the way that career volunteers make sense of who they are and what they do. These volunteers show a tendency to reject modern frames around the concepts of work, home, and volunteerism. Instead, they integrate life categories, lending an often counter-cultural conception of identity and meaning to their lives’ work.
Keywords: Volunteerism; Non profit sector; Identity; Work; Gender; Social Research (0344); Social Work (0452); Sociology (0626)